Structure and ferro/piezoelectric properties of SrBi(4)Ti(4)O(15) films deposited on TiO(2) buffer layer - Simões, Alexandre Zirpoli [UNESP]; Aguiar, E. C. [UNESP]; Riccardi, C. S. [UNESP]; Moura, F. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V. Sa, 2009)
TiO(2) buffer layer was introduced between SrBi(4)Ti(4)O(15) (SBTi) thin films and Pt bottom electrodes through the soft chemical solution. The obtained films were characterized by X-ray diffraction, atomic force microscopy and electrical properties. Unlike thin film crystallized directly onto a highly (1 1 1)-oriented Pt bottom electrode, the thin film on TiO(2) buffer layer was a single phase perovskite with random orientation. The dielectric and ferroelectric properties of the SBTi/TiO(2) thin films deposited on Pt coated Si substrates are evaluated, leading to the potential of the TiO(2) buffer layer for the integrated devices. Meanwhile, SBTi thin films deposited directly on (1 1 1) Pt bottom electrode reveal a weak ferroelectricity along c-axis direction. (C) 2008 Published by Elsevier B.V.
Keywords: Thin films; Buffer layer; Bismuth layered compounds